Open Educational Resources: Role of Libraries - Sanjeeva, Meghana; Powdwal, Sushama (Journal of Information and Knowledge, 2017)
This paper discusses awareness about Open Educational Resources (OER), the level of integration with library resources and the barriers as perceived by academic librarians. It also tries to examine the possible roles of academic libraries in promoting and supporting OER development. It presents the results of a survey on the awareness, integration and involvement of academic libraries in OER.